Therapeutic opportunities for targeting cellular senescence in progressive multiple sclerosis. (April 2022) - Sutter, Pearl A.; McKenna, Mark G.; Imitola, Jaime; Pijewski, Robert S.; Crocker, Stephen J.
Abstract: Recent studies have implicated cellular senescence as a disease-related process linked to progressive forms of multiple sclerosis (MS). Herein, we present an overview of the current pharmacopeia of cellular senescence affecting compounds and evidence for their effects, if known, in murine and cellular models of MS. Consideration is also given to the utility of these compounds for the treatment of progressive MS, with an examination of past and current clinical trials that have tested these agents, often for other purposes, in the MS patient population. Lastly, we discuss the implications and potential utility for targeting cellular senescence as a strategy to fulfil the unmet need of treatment options for the progressive MS population.